Irisin Is Correlated with Blood Pressure in Obstructive Sleep Apnea Patients - Xing Wang; Zhengjiao Zhang; Xiaoxin Lan; Keyou Fu; Guanhua Xu; Jingyi Zhao; Haibo Yuan (International Journal of Hypertension)
Background. Despite approximately 95% primary cases of hypertension, secondary hypertension seems to be common with resistant forms. Notably, obstructive sleep apnea (OSA) is known as a common cause of secondary hypertension and has a major characteristic of obesity. Irisin acts as a link between muscles and adipose tissues in obesity, playing an essential role in human blood pressure (BP) regulation. However, whether irisin is associated with secondary hypertension caused by OSA and how it takes effect essentially have not been elucidated. Purpose. To investigate the changes of irisin and its relationship with BP in OSA. Methods. 72 snoring patients finished Epworth Sleep Scale (ESS) evaluation before polysomnography (PSG). BP was the average of three brachial BP values by mercury sphygmomanometer. Serum irisin level was determined by enzyme-linked immunosorbent assay (ELISA). Results were analyzed by SPSS software. Results. Irisin was higher in the severe and quite severe group than that in control and nonsevere groups (p<0.05). For BP, significant differences were found between the control group and the other three groups (p<0.05) and between the quite severe and the other three groups (p≤0.001). Positive correlations were found between irisin and apnea-hypopnea index (AHI), AHI and BP, and irisin level and BP. Negative correlations were between irisin and SpO2 nadir and SpO2 nadir and BP. Positive correlation still existed between AHI and irisin even after adjusting for some obesity-related variables. Conclusions. Irisin may serve as a potential biomarker for severity of OSA independently of obesity and imply the development of hypertension.